13. EVALUATE EFFICIENCY OF MEDICAL PLASMA IN ABDOMINAL INCISION CARE IN CANCER PATIENTS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the supportive effect of cold plasma in wound care after abdominal surgery in cancer patients at Hợp Lực General Hospital.Materials and methods: Controlled intervention study on patients with abdominal wall incisions at the Oncology Department of Hop Luc General Hospital from January 2023 to December 2024.Results: The sensation of tightness and suture knots appeared in 8.9% of the plasma-treated group, which was lower than the 26.7% in the non-plasma group, with a statistically significant difference (p=0.027). On the 7th day after surgery, the plasma-treated group no longer felt the tension of the sutured tissue, while the group without plasma treatment still had 11.1%. The difference is statistically significant with p=0.021. The difference in early wound healing rates between the two groups was statistically significant (p
Keywords: abdominal surgery; cold plasma; cancer patients